Measuring home advantage in spanish handball - Aguilar, O. G.; Garcia, M. S.; Fernandez Romero, J. J. (Perceptual and Motor Skills, 2012)
Since Pollard established the system for analysing home advantage in 1986, it has been demonstrated and quantified in various sports, including many team sports. This study aims to assess whether home advantage exists in handball, using a sample of more than 19,000 Spanish handball league games. Results of the games played at home and away, the sex of the players, and the levels of the competition were included as variables. In Spanish handball, there was a home advantage of 61%, which means, on average, the team playing at home wins 61% of points available. This value varies according to sex and according to competition level, increasing as competition level decreases and season rank improves.